(untitled) (Research, Society and Development, 2020)
Introduction: sialochemical studies demonstrate that saliva has biomolecular proportions similar to blood, and can function as a means of diagnosing cardiovascular diseases whose factors are dyslipidemia. Objective: To assess the correlation between blood lipid concentrations and saliva. Methodology: The unstimulated saliva of 40 dentistry students, ages 18 to 29, both genders, was collected by the modified Navazesh method, then centrifuged. A venipuncture for blood collection was performed, then the blood was centrifuged and the serum separated. Labtest® kits were measured for salivary and blood cholesterol and triglycerides using the colorimetric enzymatic method. Statistically, paired Student’s t-test and Pearson’s correlation test were used. The results were expressed as mean more or less the standard error of the mean (e.p.m). Graph Pad Prism software version 6.01 was used. Results: 72.5% of the participants were female and 27.5% male, the average age was 21.55 ± 0.41 for the female gender and 21.64 ± 1.07 for the male. The average age of individuals of both genders was 21.63 ± 0.41 years. Sialometric data showed an average salivary flow of 0.71 ± 0.15 ml / min. The values of cholesterol and salivary triglycerides were significantly lower when compared to serum values and there was no correlation between these parameters. Conclusion: Saliva showed lower cholesterol and triglyceride concentrations than blood, with no significant correlation of these lipids between fluids.